2020
DOI: 10.1155/2020/9039648
|View full text |Cite
|
Sign up to set email alerts
|

Research on Wavelet Threshold Denoising Method for UWB Tunnel Personnel Motion Location

Abstract: In the process of tunnel construction, the problems of strong sealing, inconvenient communication, and harsh environment pose a serious threat to the personal safety of construction workers. erefore, personnel positioning technology has important application value in tunnel safety construction. A special environment for tunnel personnel positioning and the ultrawideband (UWB) positioning system are affected by personnel movement, which leads to the problem of lowering positioning accuracy. A wavelet threshold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Current statistics indicate that the construction industry is considerably lagged behind other major industries in technology adoption and implementation (Bosch-sijtsema et al , 2021). Previous studies suggested that incorporating advanced technology into safety management practices could offer valuable opportunities for enhancing construction safety (Asadzadeh et al , 2020; Liu et al , 2020; Martinez et al , 2020; Nnaji et al , 2020). Unfortunately, despite a plethora of safety technology-related studies, implementation of safety technologies are still limited in construction(Nnaji et al , 2019), more so in the case of the developing world (Enshassi et al , 2016; Ghansah et al , 2021; Yusof et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Current statistics indicate that the construction industry is considerably lagged behind other major industries in technology adoption and implementation (Bosch-sijtsema et al , 2021). Previous studies suggested that incorporating advanced technology into safety management practices could offer valuable opportunities for enhancing construction safety (Asadzadeh et al , 2020; Liu et al , 2020; Martinez et al , 2020; Nnaji et al , 2020). Unfortunately, despite a plethora of safety technology-related studies, implementation of safety technologies are still limited in construction(Nnaji et al , 2019), more so in the case of the developing world (Enshassi et al , 2016; Ghansah et al , 2021; Yusof et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Since GPS(Global Positioning System) signals cannot be received in an indoor environment, various indoor positioning technologies are required [1]. Common indoor wireless positioning technologies include: Wi-Fi positioning [2], Bluetooth technology [3], UWB [4], RFID, infrared positioning, RFID, ZigBee technology [5], ultrasonic and geomagnetic technology [6], etc. The current positioning algorithms mainly include nearest neighbor method [7], centroid positioning method [8], trilateral positioning method [9], triangulation method [10], fingerprint positioning method [11], dead reckoning algorithm [12], particle Group positioning algorithm [13] and neural network positioning algorithm [14], etc.…”
Section: Introductionmentioning
confidence: 99%